A New Measure of Tariff Preference Margins Adjusted for Import and Domestic Competition - Céline Carrère (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
This paper provides a new theoretically-derived measure of preference margins at the product level, that takes into account competition across exporters as well as competition with domestic producers on a given market. This indicator is derived for differentiated goods under imperfect competition, in a framework extended from Ottaviano, Tabuchi and Thisse (2002). We compute our theoretically-based preference margin measure for the European Union market access over 5,000 products (HS-6 digits) exported by an exhaustive sample of 222 countries in 2008. This new measure reveals very low preference margins once adjusted for domestic and import competition. We also provide econometric correlations validating the relevance of both our "preferred" preference margin indicator and the theoretical framework used to derive it.
Keywords: O24; F12; F15; C33; 330; Tarifs préférentiels